2019
DOI: 10.5217/ir.2019.00009
|View full text |Cite
|
Sign up to set email alerts
|

Is fecal calprotectin always normal in children with irritable bowel syndrome?

Abstract: Background/AimsFecal calprotectin (FC) is a marker of intraluminal intestinal inflammation. Intestinal inflammation may contribute to the pathophysiology of irritable bowel syndrome (IBS). This study evaluated FC levels in children with IBS and differences in FC levels in children stratified by IBS subtype and healthy controls (HCs).MethodsA total of 157 children with IBS and 56 HCs aged 4–16 years (119 boys, 94 girls, mean age of 9.48 years) were included in this prospective study. Children with IBS were diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…While a low calprotectin decreases the chances of IBD (particularly in combination with a low CRP), it does not eliminate IBD from the diagnosis; similarly an elevated calprotectin does not necessarily indicate IBD, particularly in patients with diarrhea-predominant IBS. 55 , 58 , 61 While most studies do not support a relationship between celiac disease and pediatric FAPDs, one Italian study found a 4-fold increase in celiac (4.4% vs 1%) in youth with IBS and another study found a borderline increase. 62 , 63 Both the American Gastroenterological Association (AGA) and the pediatric Rome committee have recommended celiac screening in IBS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While a low calprotectin decreases the chances of IBD (particularly in combination with a low CRP), it does not eliminate IBD from the diagnosis; similarly an elevated calprotectin does not necessarily indicate IBD, particularly in patients with diarrhea-predominant IBS. 55 , 58 , 61 While most studies do not support a relationship between celiac disease and pediatric FAPDs, one Italian study found a 4-fold increase in celiac (4.4% vs 1%) in youth with IBS and another study found a borderline increase. 62 , 63 Both the American Gastroenterological Association (AGA) and the pediatric Rome committee have recommended celiac screening in IBS.…”
Section: Discussionmentioning
confidence: 99%
“…54 Serum C-reactive protein (CRP) and stool calprotectin or stool lactoferrin also have utility in indicating IBD including in children and adolescents. [55][56][57][58][59][60] However, results must be interpreted with caution. While a low calprotectin decreases the chances of IBD (particularly in combination with a low CRP), it does not eliminate IBD from the diagnosis; similarly an elevated calprotectin does not necessarily indicate IBD, particularly in patients with diarrhea-predominant IBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent study demonstrated that differences in fecal calprotectin concentrations in children discriminated between IBS subtypes and from healthy controls. In particular, fecal calprotectin concentration was highest in IBS-D, followed by those with IBS-M and IBS-C (Choi and Jeong, 2019 ). In combination with other plasma and fecal biomarkers, fecal calprotectin may effectively discriminate IBS from health and within IBS subtypes (Nemakayala and Cash, 2019 ).…”
Section: Biomarkers Toward An Immune Signature In Functional Gastroinmentioning
confidence: 99%
“…[ 30 , 31 ] This means that intestinal inflammation may also contribute to the pathophysiology of IBS. [ 11 ] In a study by Choi et al, [ 32 ] fecal calprotectin was used to assess intestinal inflammation in pediatric IBS patients. Fecal calprotectin levels were significantly higher among IBS patients than healthy controls, and the values were distributed in the intermediate range (50–150 µg/g), confirming that IBS was also associated with low-grade bowel inflammation.…”
Section: Discussionmentioning
confidence: 99%